2023
DOI: 10.3390/antibiotics12111585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Tests for the Rapid Detection of CTX-M Producers Directly in Urine Samples

Forrest Tang,
Chung-Ho Lee,
Xin Li
et al.

Abstract: Infections caused by extended-spectrum β-lactamase-producing Enterobacterales have increased rapidly and are mainly attributed to the production of CTX-M enzymes. This study evaluated the NG-Test® CTX-M MULTI lateral flow assay (CTX-M LFA) and the Rapid ESBL NP® test (ESBL NP test) for rapid detection of CTX-M-producing Enterobacterales directly in midstream urine (MSU) samples. Testing was performed on 277 clinical MSU samples in a hospital microbiology laboratory from November 2022 to January 2023; 60 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This approach demonstrated a sensitivity of 100% (95% CI: 91.19%–100%) and a specificity of 95% (95% CI: 95.6%–100%) for beta-lactamase detection. 11 In our study, we observed a sensitivity of 87.5% with a specificity of 100%. A key difference in our research is that we used 1 mL of urine instead of 3 mL and included samples with a bacterial load ≥10 4 cfu/mL.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This approach demonstrated a sensitivity of 100% (95% CI: 91.19%–100%) and a specificity of 95% (95% CI: 95.6%–100%) for beta-lactamase detection. 11 In our study, we observed a sensitivity of 87.5% with a specificity of 100%. A key difference in our research is that we used 1 mL of urine instead of 3 mL and included samples with a bacterial load ≥10 4 cfu/mL.…”
Section: Discussionsupporting
confidence: 54%
“…Tang et al . 11 recommend a prior enrichment step involving centrifugation of 10 mL urine at 3000 × g for 15 min, discarding the supernatant and additional incubation at 37°C for 20 min to enhance the sensitivity. However, this contradicts the POCT principle, as it requires equipment like a centrifuge and an incubator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation